A Fuzzy Scheduling Method for Pipeline Processing in Shipyards Incorporating the Black Widow Optimization Algorithm - Chunli Meng; Zhiqiang Feng; Daidi Zhao; Xin Li; Jianxing Yu; Lijun Yang (Applied Sciences, 2024)
In the process of ship production, the production of pipeline occurs throughout the production process. Key issues to address in the pipeline-processing workshop of a shipyard include uneven production loads and weak flow rhythmicity. Additionally, uncertainties in processing time and other real-world factors can pose significant challenges. The fuzzy number method is used to describe processing and completion times, with the goal of minimizing the fuzzy maximum completion time. To achieve this, a scheduling method based on the Black Widow Optimization Algorithm (BWOA) is proposed for the pipeline-processing workshop in a shipyard. This algorithm aims to effectively reduce the blindness of the production plan, ensure the rationality and stability of the plan, shorten the production cycle of a ship pipeline, improve the production efficiency, and realize the lean shipbuilding mode. A simulation was conducted to evaluate the BWOA algorithm. The final simulation test results show that the algorithm provided a better scheduling plan and a stabler average value than comparable methods, which proves its effectiveness in the scheduling of pipeline processing in shipyards.